Oral Health Status and Treatment Needs among 12 and 15-year-old Government and Private School Children in Rupandehi District (Bhairahawa) Nepal - Halwai, HK; Bhat, PK; Shekhar, M; Yadav, B (Journal of Universal College of Medical Sciences, 2014)
INTRODUCTION : Good oral health is important and have major impact on peoples daily lives and activities. This study  was conducted to assess dental caries, periodontal health, and malocclusion of school children aged 12 and 15 years and to compare them in government and private schools. MATERIAL AND METHODS: A cross-sectional study of 12- and 15-year-old children in government and private schools was conducted in Rupendehi (Bhairahawa) Nepal. A sample of 1011 school children (both males and females) was selected by a two-stage cluster sampling method. Clinical recordings of dental caries and malocclusion were done according to World Health Organization diagnostic criteria 1997. Periodontal health was assessed by Community Periodontal Index of Treatment Needs index. The data collected was analyzed by SPSS versons 13. The statistical tests used were t-test and Chi-square tests.RESULTS: The prevalence of dental caries was 32.6% and 42.2% at 12 and 15 years of age, respectively. At 12 years of age, the mean decayed, missing, filled teeth were 0.62 ± 1.42 and it was 1.06 ± 2.93 at 15 years of age. Females had higher level of caries than males at both the ages. At both ages, mean of decayed teeth was statistically higher in government schools as compared with private schools. Children in government schools had significantly less number of mean filled teeth at both ages as compared with private schools. The healthy component of gingiva was present in higher percentage of children in private schools as compared with government schools at both the age groups. The prevalence of malocclusion among the 12- year-old (58.1%) was more as compared with that among the 15-year-old (53.5%).CONCLUSION: The caries experience of 12 and 15 years old children was low but the prevalence of gingivitis and malocclusion was quite high. Effective oral health promotion strategies need to be implemented to improve the oral health of school children further in Rupendehi District , Bhairahawa, Nepal.DOI: http://dx.doi.org/10.3126/jucms.v2i3.11822 Journal of Universal College of Medical Sciences Vol.2(3) 2014: 15-19